How Great are Implication Factors for Employee Engagement in Application-Based Technology Company? - Ahmad Azmy (Bina Nusantara University, 2022)
Dimensions of organizational culture, training and development, job environment, and supervisor relationship have implications for employee engagement. Employee engagement is needed to produce high-quality work results in the application company. The purpose of the research was to analyze the factors with implications for employee engagement. The research objective was an application-based technology company in Indonesia. The sampling approach used a stratified method. Then, the number of respondents was 100 people. Meanwhile, the analysis method applied Partial Least Square (PLS). The results reveal that four variables have implications for employee engagement. The training and development dimension has the highest implications for employee engagement. The company must implement organizational culture in accordance with its core business values. Then, the conduciveness of the work environment must be increased to provide a positive psychological effect for employees. Similarly, supervisor relationships must be well maintained to monitor the work process. These four variables prove that the application-based technology company needs an increase in employee engagement to generate new business ideas. Innovation and creativity can be generated through employee engagement. The conclusion is that application-based technology company must pay attention to the application of culture organization and the sustainability of training and development programs, provide a comfortable job environment, and maintain supervisor relationships with their employees.